Understanding the Needs of Science Access Students for University Support Services - Chetty, Yvette; Vigar-Ellis, Debbie (South African Journal of Higher Education, 2016)
The need to develop science capacity in South Africa has been recognised as a national priority both to address past inequalities and for economic development. However, many students wanting to enter science–related programmes in universities lack the necessary skills, knowledge and resources and thus access programmes have been developed to bridge the gap. This research takes a marketing approach and thus seeks to establish the needs of science access students at the point of entry into the university. An exploratory design using questionnaires administered to the population of students enrolled for the University of KwaZulu-Natal’s, Science Foundation Programme, was used. Analysis of the results indicates that the most important needs of these students are for career and counselling advice, financial support and information. Recommendations are provided to universities on how to address these needs so as contribute positively to the development of science capacity in South Africa. Key words Science Access, Student needs, Access programmes